The Role of Dividend Policy and Managerial Ownership on Company Value in the Finance Sector - N F Salsabila; J Kadang; Munawarah; C R K Bidin (Universitas Muhammadiyah Palu, 2024)
Company value has an important role in increasing investors' confidence in seeing how successful a company is. This research aims to determine the role of dividend policy and managerial ownership on the value of companies in the finance sector listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique in this research used purposive sampling and a sample of 96 observation data was obtained from 8 companies. The data analysis method used is quantitative analysis and research data is analyzed using the panel data regression method which is a combination of time series and cross-section data. Time series data is data collected from time to time on an individual, while cross-section data is data collected from time to time on a large number of individuals. The results of this study show that dividend policy and managerial ownership simultaneously have a positive and significant effect on the value of the company. Partially, dividend policy has a positive and significant effect on company value, while the managerial ownership variable partially has a positive but not significant effect on company value.